Implementasi Text-To-Speech Menggunakan Responsive Voice Pada Aplikasi Novel Berbasis Web - Sigit Ardiansyah; Andriani (Teknik Informatika, Universitas Pelita Bangsa, 2023)
Novels are fictional books that provide entertainment and offer unique experiences. However, many individuals face limitations in reading due to health issues, lack of time, or reading abilities. Web-based novel applications serve as an alternative for online reading, but they are not effective for individuals with reading limitations. This research aims to implement text-to-speech technology in web-based novel applications to assist individuals with reading limitations in enjoying novels more comfortably and easily. The Agile method is employed in software development, emphasizing collaboration, adaptation, and delivering high business value. The results of this research demonstrate that the implementation of text-to-speech in web-based novel applications enhances accessibility for users with visual impairments or reading difficulties. Additionally, users can multitask and customize their reading experience according to their personal preferences. These advantages can expand the target market of novel applications and stimulate interest in reading within the community. Keywords: Novel, Reading Limitations, Text-to-speech, Agile